Samuel Bailey on Appreciation - Mixter, C. W. (Quarterly Journal of Economics, 1898)
Samuel Bailey on Appreciation Get access C. W. Mixter C. W. Mixter Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 12, Issue 3, April 1898, Pages 343–348, https://doi.org/10.2307/1881898 Published: 01 April 1898